Treatment of cognitive impairment in the early postoperative period - L. V. Roshkovskaya; I. V. Sheverova; D. V. Zakharov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
On the basis of SPb GUZ «Nikolayevskaya hospital» assessed the efficacy and tolerability of the drug Gliatilin in the early postoperative period in patients undergoing General anesthesia for 2-2,5 hours. The study included 56 patients who received operative treatment in abdominal organs, mainly cholecystectomy, with transfusion therapy within 2-2,5 hours. All patients received anesthesia with Diprivan in a concentration of 1.5-2 mg/kg/h. Compared groups were statistically homogeneous for sex, age and baseline neuropsychiatric status (p